If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7q * 3q = 0 Reorder the terms for easier multiplication: 7 * 3q * q = 0 Multiply 7 * 3 21q * q = 0 Multiply q * q 21q2 = 0 Solving 21q2 = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Divide each side by '21'. q2 = 0 Simplifying q2 = 0 Take the square root of each side: q = {0}
| 1.1-4x-3.1-2x=-5x-3.3 | | 2(4z+4)-9=39 | | 2x+4y=106 | | (x*x)-6x=0 | | 92*67*67*67*98*75*57*23*34= | | 5y+6=6y-14 | | 2/5b-6-2 | | ln(3x-18)=8 | | 2(2x+2)=4x+6-2 | | (x^2-5)(x^2-4x+5)=0 | | 12x+12-x-5=92 | | 106=41(2x+4y) | | 5+x=87 | | 2-k=0 | | 2(x^2-5)(x^2-4x+5)=0 | | a^2+a+a^2=0 | | 36/3/5 | | 155.00x+7500.00=92440.00 | | X*2+5=-14 | | 39.55+0.20m=80 | | x^(2/3)-1 | | 15+3=18y | | 5b+3(4+5b)= | | x^2=7-2x | | 2x^7-16x^6+12x^5= | | 5+3(4+5)= | | (-15/2)(-1) | | 7x+1x=28+9x | | (324*80)= | | 2x^4-8x^3+40x-50=0 | | 7x+1x=14+9x | | 2.583+(-5.399)= |